2012
DOI: 10.1038/ismej.2012.142
|View full text |Cite
|
Sign up to set email alerts
|

Gut bacteria–host metabolic interplay during conventionalisation of the mouse germfree colon

Abstract: The interplay between dietary nutrients, gut microbiota and mammalian host tissues of the gastrointestinal tract is recognised as highly relevant for host health. Combined transcriptome, metabonome and microbial profiling tools were employed to analyse the dynamic responses of germfree mouse colonic mucosa to colonisation by normal mouse microbiota (conventionalisation) at different time-points during 16 days. The colonising microbiota showed a shift from early (days 1 and 2) to later colonisers (days 8 and 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 57 publications
(63 reference statements)
4
83
0
Order By: Relevance
“…In addition, previous studies using Gn and conventionalized mice revealed major molecular responses in metabolism, intestinal morphology and cell proliferation, and immunity as early as days 1-4 postconventionalization, with pronounced changes occurring after day 4 post-conventionalization. 57,58 Consistent with these findings, in our study more robust responses were observed on PBCD7, particularly in duodenum, illustrating the tissue-specific changes in the biological processes. However, detailed temporal analysis of transcriptome responses to lactobacilli colonization in neonatal Gn and conventional pigs (mimicking the infants) would provide better understanding of the biological processes modulated by these known probiotics.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, previous studies using Gn and conventionalized mice revealed major molecular responses in metabolism, intestinal morphology and cell proliferation, and immunity as early as days 1-4 postconventionalization, with pronounced changes occurring after day 4 post-conventionalization. 57,58 Consistent with these findings, in our study more robust responses were observed on PBCD7, particularly in duodenum, illustrating the tissue-specific changes in the biological processes. However, detailed temporal analysis of transcriptome responses to lactobacilli colonization in neonatal Gn and conventional pigs (mimicking the infants) would provide better understanding of the biological processes modulated by these known probiotics.…”
Section: Discussionsupporting
confidence: 90%
“…2, Table S2). Supporting this hypothesis, consistently higher tryptophan levels in urine were reported during the establishment of a gut microbiota compared with germfree animals 36 though another study reported lower serum tryptophan levels in conventional mice compared to germfree mice. 37 Interestingly, ex-germfree mice also displayed higher levels of phenylalanine, tyrosine, and tryptophan in the cerebral metabolome compared with germfree mice.…”
Section: Discussionmentioning
confidence: 88%
“…Proteobacteria was the most abundant phylum in breast tissue, unlike in the vagina, oral cavity, bladder, skin, and gastrointestinal tract, where members of this phylum make up only a small pro- portion of the overall bacterial community (5,8,(31)(32)(33)(34) (36). It has also been documented that wild-type mice fed a high-fat diet have a gut microbiota enriched in Firmicutes (37).…”
Section: Discussionmentioning
confidence: 99%